Genetic deletion of p66shc and/or cyclophilin D results in decreased pulmonary vascular tone. Issue 1 (29th October 2020) - Gierhardt, Mareike; Pak, Oleg; Sydykov, Akylbek; Kraut, Simone; Schäffer, Julia; Garcia, Claudia; Veith, Christine; Zeidan, Esraa M; Brosien, Monika; Quanz, Karin; Esfandiary, Azadeh; Saraji, Alireza; et al.
Abstract: Aims: The pulmonary vascular tone and hypoxia-induced alterations of the pulmonary vasculature may be regulated by the mitochondrial membrane permeability transition pore (mPTP) that controls mitochondrial calcium load and apoptosis. We thus investigated, if the mitochondrial proteins p66shc and cyclophilin D (CypD) that regulate mPTP opening affect the pulmonary vascular tone. Methods and results: Mice deficient for p66shc (p66shc −/− ), CypD (CypD −/− ), or both proteins (p66shc/CypD −/− ) exhibited decreased pulmonary vascular resistance (PVR) compared to wild-type mice determined in isolated lungs and in vivo . In contrast, systemic arterial pressure was only lower in CypD −/− mice. As cardiac function and pulmonary vascular remodelling did not differ between genotypes, we determined alterations of vascular contractility in isolated lungs and calcium handling in pulmonary arterial smooth muscle cells (PASMC) as underlying reason for decreased PVR. Potassium chloride (KCl)-induced pulmonary vasoconstriction and KCl-induced cytosolic calcium increase determined by Fura-2 were attenuated in all gene-deficient mice. In contrast, KCl-induced mitochondrial calcium increase determined by the genetically encoded Mito-Car-GECO and calcium retention capacity were increased only in CypD −/− and p66shc/CypD −/− mitochondria indicating that decreased mPTP opening affected KCl-induced intracellular calcium peaks in these cells. All mouse strains showed a similar pulmonary vascular response to chronic hypoxia, while acute hypoxic pulmonary vasoconstriction was decreased in gene-deficient mice indicating that CypD and p66shc regulate vascular contractility but not remodelling. Conclusions: We conclude that p66shc specifically regulates the pulmonary vascular tone, while CypD also affects systemic pressure. However, only CypD acts via regulation of mPTP opening and mitochondrial calcium regulation. Graphical Abstract: